Effectiveness of Cold Compress with Ice Gel on Pain Intensity among Patients with Post Percutaneous Coronary Intervention (PCI) - Gentur Wicaksono; Ta’adi Ta’adi; Masrifan Djamil (International Journal of Nursing and Health Services (IJNHS), 2020)
Coronary heart disease is caused by narrowing the coronary arteries due to atherosclerosis or spasms, or a combination of both. A non-surgical intervention to reopen narrowed coronary arteries by Percutaneous Coronary Intervention (PCI) and pain is one of the common symptoms. Interventions were carried out to reduce pain by using cold compresses with ice gel. This study aimed to examine the effect of cold compress with ice gel on pain intensity among patients with aff femoral sheath post-Percutaneous Coronary Intervention (PCI). True experimental approach post-test only with control group design was applied in this study. Independent t-test showed a significant difference p-value 0.000 (<0.05) that the pain intensity of the intervention group decreased from 4.53 to 2.40 (p=0.000) with a mean delta value of -2.13. The mean pain intensity control group also reduced from 4.40 to 4.27 (p=0.334) with a mean delta value of -0.13. Conclusion cold compresses with ice gel effectively reduce pain intensity in aff femoral sheath patients with post percutaneous coronary intervention (PCI). Cold compress (ice gel) is a nurse's independent action to reduce the pain intensity scale and increase comfort during the treatment phase but still requires collaboration with doctors to provide analgesics